Behind the Politics of Resilience: the Limits of the EU's Response to Syrian Refugees in Lebanon. (27th December 2022) - André, Lyla
Abstract: The Syrian crisis that began expanding in 2012 has sent millions of refugees into neighbouring countries and beyond and proved to be a testing ground for the European Union's new approach to humanitarian crises. Focused on European Union-funded educational programmes carried out in response to the Syrian refugee crisis in Lebanon, this article argues that the European Union's approach has nevertheless negatively impacted refugees' lives because of its embeddedness in the international regime of resilience that has gained ground in the field of refugee protection. Indeed, while the resilience regime appears to be a continuation of the neoliberal system of rule, it in fact represents a paradigmatic shift that implies political and moral retreat from donors' responsibility. Applied to refugee management, the agenda of "resilience" thus contradicts the rationale for burden-sharing that previously involved a "shared responsibility" between external donors and the hosting State. Based on Kratochwil's praxis approach, this article therefore aims to empirically expand upon the recent literature centred on "resilience" and "self-reliance" in the field of refugee management. In doing so, it demonstrates how neoliberal features of resilience further hinder refugees' lives as these features entail a total separation from an adequate rights-based approach.